Mechanistic target of rapamycin signaling in mouse models of accelerated aging. (1st March 2019) - Lee, Jin Young; Kennedy, Brian K; Liao, Chen-Yu
Abstract: The mechanistic target of rapamycin (mTOR) is an essential nutrient-sensing kinase that integrates and regulates a number of fundamental cellular processes required for cell growth, cell motility, translation, metabolism, and autophagy. mTOR signaling has been implicated in the progression of many human diseases, and its dysregulation has been reported in several pathological processes, especially in age-related human diseases and mouse models of accelerated aging. In addition, many studies have demonstrated that the regulation of mTOR activity has a beneficial effect on longevity in several mouse models of aging. However, not all mouse models of accelerated aging show positive effects on aging-associated phenotypes in response to targeting mTOR signaling. Here, we review the effects of interventions that modulate mTOR signaling on aging-related phenotypes in different mouse models of accelerated aging and discuss their implications with respect to aging and aging-related disorders.